(untitled) (KONFERENSIYA, 2025)
Abdulla Qodiry’s O‘tgan kunlar (1925) is regarded as the first full-fledged Uzbek novel and a foundational work of modern Uzbek literature. The novel is rich with allusions indirect references to historical, religious, literary, and cultural sources that deepen its ideological message and connect the fictional world to the real social, moral, and spiritual struggles of the late 19th century. This article explores the major types of allusions in the novel, analyzing their functions, meanings, and artistic effects within the narrative